Low access to animal protein, oils and snack caused stunted among 25-59 months old children in Jakarta urban slum during pandemic - Ratnayani, Ratnayani; Sunardi, Diana; Agestika, Lina (International Journal of Innovative Research and Scientific Studies, 2025)
Children aged 23-59 months were disproportionately affected by stunting during the COVID-19 pandemic due to economic hardship. This study aimed to investigate the association between food expenditure and the type of food source with stunting among under-five children in Jakarta slums. A comparative cross-sectional design was employed to analyze data from 42 pairs of under-five children and their mothers. Information on household expenditure and food consumption was collected through questionnaires. Statistical comparisons between stunted and non-stunted groups were conducted using independent t-tests and the Mann-Whitney U test. The study revealed a significantly lower overall food expenditure among stunted children compared to their non-stunted counterparts. Notably, spending on animal-based foods and snacks was considerably lower in the stunted group. These findings were confirmed by child nutrient intake, which showed significant differences in energy and macronutrient consumption from animal sources between the two groups. The results highlight the critical role of food expenditure and dietary quality in preventing stunting, particularly in vulnerable populations. In challenging economic conditions, prioritizing allocations for nutrient-dense foods, such as those derived from animal sources, is essential.